2017
DOI: 10.1002/polb.24346
|View full text |Cite
|
Sign up to set email alerts
|

In situ grazing incidence small‐angle X‐ray scattering study of solvent vapor annealing in lamellae‐forming block copolymer thin films: Trade‐off of defects in deswelling

Abstract: Solvent vapor annealing (SVA) is one route to prepare block copolymer (BCP) thin films with long‐range lateral ordering. The lattice defects in the spin‐coated BCP thin film can be effectively and rapidly reduced using SVA. The solvent evaporation after annealing was shown to have a significant impact on the in‐plane ordering of BCP microdomains. However, the effect of solvent evaporation on the out‐of‐plane defects in BCPs has not been considered. Using grazing‐incidence x‐ray scattering, the morphology evolu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 37 publications
(48 reference statements)
0
12
0
Order By: Relevance
“…In this work, MNP-DBC hybrid magnetic films with various particle concentrations are established by a printing technique, enabling control over the film thickness. Previous studies showed that the incorporation of MNPs can change the orientation of the printed polymer nanostructures. , Also SVA was reported in literature as a powerful tool to tune the order and orientation of polymer nanostructures. We use both approaches to control the final architecture of the hybrid films. For this purpose, all films are printed with a thickness close to the periodic interdomain distance of the DBC.…”
Section: Resultsmentioning
confidence: 99%
“…In this work, MNP-DBC hybrid magnetic films with various particle concentrations are established by a printing technique, enabling control over the film thickness. Previous studies showed that the incorporation of MNPs can change the orientation of the printed polymer nanostructures. , Also SVA was reported in literature as a powerful tool to tune the order and orientation of polymer nanostructures. We use both approaches to control the final architecture of the hybrid films. For this purpose, all films are printed with a thickness close to the periodic interdomain distance of the DBC.…”
Section: Resultsmentioning
confidence: 99%
“… 35 Finally, the last stage, direct casting, i.e ., the transition from dynamically evolving to a vitrified state, is likely important for the resulting BCP morphology analogously to the SVA experiments in which the rate of solvent removal is critical for the preservation of the ordered structure and, in the limiting cases, can be disrupted upon drying. 36 , 37 , 97 …”
Section: Discussionmentioning
confidence: 99%
“…For example, solvent removal rate at the end of SVA experiment has been demonstrated to determine the orientation of cylinder-forming poly(styrene-b-isoprene-bstyrene) triblock copolymer, 55 cylinder-gyroid phase selection and domains' orientation in PS-b-PLA, 56 sphere packing in asymmetric PS-b-P4VP, 28 and the relative in-and out-of-plane defectivity in lamellae-forming P2VP-b-PS-b-P2VP triblock. 37 The selection of a proper solvent or solvent mixture composition is critical in solvent-driven DSA methods outlined above. Its role is not only plasticization of the system by lowering the glass-transition temperature and increasing chain diffusivity but also affecting the chemical interactions between the BCP blocks.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thermal or solvent annealing is then used to permit domain reorganization. Thermal annealing is energy intensive and can lead to degradation, , while solvent vapor annealing (SVA) can drive the assembly at lower temperatures, and equilibrium structures are obtained much faster. A wide range of processing conditions can influence self-assembly during solvent annealing, such as solvent quality for either block, , exposure time, solvent vapor pressure, , film thickness, , annealing method (e.g., SVA versus direct immersion annealing , ) and polymer chemistry. , The results are a rather extensive, though often incomplete, phase space for this process.…”
mentioning
confidence: 99%